Development of Fe-5Al-1C alloys for grinding ball - Kartikasari, Ratna; Subardi, Adi; Wijaya, Andy Erwin (Eastern-European Journal of Enterprise Technologies, 2021)
Our object of research is to combine the properties of Mn and the advantages of Fe-Al-C to improve the performance of grinding ball materials. Three Fe-5Al-1C alloys with compositions of 15 wt% Mn (FAM15), 20 wt% Mn (FAM20), and 25 wt% Mn (FAM25) were investigated. Argon gas was used to assist the removal of dissolved oxygen and to control the formation of metal oxides during Fe-Al-Mn-C (FAMC) fabrication. Microstructure analysis was conducted using scanning electron microscopy, and the Vickers microhardness tester was used to evaluate hardness. To guarantee the Fe-5Al-1C-Mn alloy phase, X-ray diffraction (XRD) test was performed. The EDS test was carried out to show the composition at different points and to observe the presence of several phases in the FAMC alloy system. A pin-on-disc method was employed for a dry sliding wear test, and corrosion testing was performed using the three-electrode cell polarization method. With the addition of Mn, the Vickers hardness of the FAMC alloy raised from 194.4 VHN at 15 wt% to 265 VHN at 25 wt%. The tensile strength and fracture elongation values were 424.69 MPa, 27.16 % EI; 434.72 MPa, 33.6 % EI; and 485.71 MPa, 38.48 % EI for FAM15, FAM20, and FAM25, respectively. A crucial factor for increasing the performance of grinding ball is the wear mechanism. The wear rate results for FAM25 show a decline of more than 57 % compared to FAM15 due to an increase in the hard intermetallic area. The addition of Mn elements increased the corrosion resistance of the FAMC alloys; the lowest corrosion rate occurred at 25 wt% Mn content at up to 0.036 mm/yr. According to the experimental results, the FAM25 alloys have the highest mechanical and corrosion resistance of the three types of alloys. The FAMC alloy is a promising candidate for application as a material for grinding balls by optimizing the Mn content